Optimizing the Role of MSMEs in an Efforts to Revive the National Economic during the Pandemic of Covid-19 - Sundari, Sri (Dinasti International Journal of Economics, Finance & Accounting, 2022)
Economic development is a top priority for every country. Due to this urgency state, this research aims to investigate whether MSMEs plays crucial part in Reviving the national economic during the COVID-19 pandemic in Indonesia. The research method used was qualitative with descriptive analysis based on literature study. The research approach used is an integral comprehensive approach. So that it comes to the results which indicate that MSMEs have a tremendous contribution to the national economic especially in the recovery time after being hit by the pandemic. The abundance of MSMEs in Indonesia is inseparable from numerous challenges and circumstance of the Covid-19 pandemic which modified the consumption pattern towards goods and services into a momentum in accelerating the digital transformation. Therefore, MSMEs are advised to encourage the progressing of MSMEs in order to advance its class through acceleration of digital transformation and capacity building.